1. 向量a=(2cos(-θ),2sin(-θ))=(2cosθ,-2sinθ);向量b=(cos(90°-θ),sin(90°-θ)=(sinθ,cosθ).
|a|=√[2cosθ)^2+(-2sinθ)^2].
=√4(cos^2θ+sin^2θ).
∴|a|=2;
|b|=√(cos^2θ+sin^2θ).
∴|b|=1
2. 证:∵a.b=2cosθsinsθ-2sinθcosθ=0.
∴a⊥b.
3. x=a+(t^2-3)b.
=(2cosθ,-2sinθ)+(t^2-3)(sinθ,cosθ).
=(2cosθ+(t^2-3)sinθ,-2sinθ+(t^2-3)cosθ).
y=-a+tb
=-k(2cosθ,-2sinθ)+t((sinθ,cosθ)=((-2kcosθ,2ksinθ)+(tsinθ,tcosθ)).
=((-2kcosθ+tsinθ, 2ksinθ+tcosθ)).
∵ 向量x,向量y满足向量x⊥向量y,∴x.y=0.
化简后,得:(t^2-3)=4k/t.
k=(t^3-3t)/4.
(k+t^2)/t={[(t^3-3t)/4]+t^2}/t.
=(1/4)(t^2+4t-3).
=(1/4)[(t+2)^2-7].
=(1/4)(x+2)^2-7/4.
当t=-2时,(k+t^2/t)具有最小值(-7/4).